Non-coding RNA in Fragile X Syndrome and Converging Mechanisms Shared by Related Disorders - Zhou, Yafang; Hu, Yacen; Sun, Qiying; Xie, Nina (Frontiers in Genetics, 2019)
Abstract Fragile X syndrome (FXS) is one of the most common forms of hereditary intellectual disability. It is also a well-known monogenic cause of autism spectrum disorders. Repetitive trinucleotide expansion of CGG repeats in the 5’-UTR of FMR1 is the pathological mutation. Full mutation CGG repeats epigenetically silence FMR1 and thus lead to the absence of its product, fragile mental retardation protein (FMRP), which is an indispensable translational regulator at synapsis. Loss of FMRP causes abnormal neural morphology, dysregulated protein translation, and distorted synaptic plasticity, giving rise to FXS phenotypes. Non-coding RNAs, including siRNA, miRNA, and lncRNA, are transcribed from DNA but not meant for protein translation. They are not junk sequence but play indispensable roles in diverse cellular processes. FXS is the first neurological disorder being linked to miRNA pathway dysfunction. Since then, insightful knowledge has been gained in this field. In this review, we mainly focus on how non-coding RNAs, especially the siRNAs, miRNAs, and lncRNAs, are involved in FXS pathogenesis. We would also like to discuss several potential mechanisms mediated by non-coding RNAs that may be shared by FXS and other related disorders.